Colonial encounters in ancient Iberia : Phoenician, Greek, and indigenous relations (University of Chicago Press, 2009)
Situating ancient Iberia within Mediterranean colonial history & establishing a theoretical framework for approaching encounters between colonists & natives, these studies exemplify the new intellectual vistas opened by the engagement of colonial studies with Iberian history